Empowerment Evaluation: A Case Study of Citywide Implementation Within an HIV Prevention Context. (September 2019) - Phillips, Gregory; Lindeman, Peter; Adames, Christian N.; Bettin, Emily; Bayston, Christopher; Stonehouse, Patrick; Kern, David; Johnson, Amy K.; Brown, C. Hendricks; Greene, George J.
HIV continues to significantly impact the health of communities, particularly affecting racially and ethnically diverse men who have sex with men and transgender women. In response, health departments often fund a number of community organizations to provide each of these subgroups with comprehensive and culturally responsive services. To this point, evaluators have focused on individual interventions but have largely overlooked the complex environment in which these interventions are implemented, including other programs funded to do similar work. The Evaluation Center was funded by the City of Chicago in 2015 to conduct a citywide evaluation of all HIV prevention programming. This article will describe our novel approach to adapt the principles and methods of the empowerment evaluation approach, to effectively engage with 20 city-funded prevention programs to collect and synthesize multisite evaluation data, and ultimately build capacity at these organizations to foster a learning-focused community.